Tribute and trade : China and global modernity, 1784-1935 - Christie, William, 1952-; Christie, William, 1952-; Dunstan, Angela; Tong, Q. S.; Tong, Q. S. (China and the West in the modern world., 2020)
P>Tribute and Trade: China and GlobalModernity explores encounters between China and the West during thisperiod and beyond, into the early 20th century, through examples drawn fromart, literature, science, politics, music, cooking, clothing and more.